Turkey’s role in the european security and defence policy - Akgül, Öner (My University, 2008)
Bu yüksek lisans çalışmasının amacı, 1990’larda gelişmeye başlayan ve 1998’den sonra özerk hale gelmeye başlayan yeni Avrupa güvenlik mimarisini açıklarken, bu süreçte Türkiye’nin rolünü ortaya koymaktır. Bu bağlamda Türkiye’nin AGSP’ye katılımı değerlendirilmektir. Çalışma birbiriyle bağlantılı birden fazla argüman üzerine kuruludur. Buna göre, AGSK’nın, AB üyesi olmayan Avrupalı Müttefiklerin, yeni Avrupa güvenlik yapısına katılımları açısından daha tatmin edici olduğu savunulmaktadır. AB’nin kendi

imkân ve kabiliyetlerini geliştirebilmesi, NATO’dan bağımsız bir askeri yapılanma kurulması noktasında önem kazanmaktadır. NATO’dan bağımsız bir savunma yapısı, NATO ile AB arasındaki dengeyi bozmakta, bu bağlamda, NATO ile AB arasında bulunan dengenin bozulması en çok bu ülkeleri etkilemektedir. Bu ülkelerden birisi olan Türkiye’nin, AB ile olan ilişkileri, jeopolitik konumu ve askeri potansiyeli dikkate alındığında diğer ülkelerden farklı ve benzersiz olduğu ortaya çıkmaktadır. Ancak, Türkiye AB’nin geliştirdiği özerk AGSP yapısının dışında tutulmuştur. Bu bilgiler ışığında temel argüman, Türkiye’nin AB’ye tam üye olmadan AGSP’ye tam katılımının mümkün olmadığıdır. Bu bilgiler ışığında çalışma, toplam üç bölümden oluşmaktadır. Birinci bölümde 1990 ile 1999 arasında geçen süreçte, AGSP’nin erken gelişim dönemi ortaya konmuş, Transatlantik bağının korunması amacıyla ortaya konan çözümler açıklanmıştır. İkinci bölümde NATO’nun dışında özerk olarak geliştirilen AGSP yapısının geliştirilme ve uygulama süreci incelenmiştir. Üçüncü ve son bölümde ise ilk iki bölümde açıklanan AGSP içerisinde Türkiye’nin rolünün ne olduğu ortaya konmakta ve Türkiye-AB ilişkilerine güvenlik boyutundan bakılmaktadır. ABSTRACT This study aims to analyze Turkey’s role in the new European security architecture which began to develop in 1990s and became autonomous after 1998. In this context, it is argued that the European Security and Defense Identity (ESDI) was a satisfactory option with regard to the participation of non-EU European Allies in the new European security structure. The improvement of the ESDP capabilities is vital for the EU. Because, the EU needs NATO’s assets and capabilities, this dependence to NATO capabilities restricts the development of ESDP as a autonomous body for the EU. EU’s desire to obtain an autonomous defense structure damaged the NATO-EU relations. In this regard, the breakdown of equilibrium between NATO and the EU mostly affected the non-EU European Allies. At this point, Turkey, which is one of these countries, enjoys a peculiar position concerning its relations with the EU, its geostrategical location and its military potential. However, Turkey was excluded from the autonomous European security structure. In this context, the basic argument is the problem over Turkey’s participation in the ESDP can not be resolved before Turkey becomes a full member of the EU. This study consists of three chapter with regard to development of the ESDP and Turkey’s role in this process. First and foremost, it attempts to explain what the ESDP is and how it has developed. Understanding the structure and development of the ESDP facilitates the explanation of Turkey’s role in this process. For this reason, the early development process of the ESDP is portrayed in the first chapter through examining the NATO’s and the EU’s core documents on this issue. The second chapter concentrates on the improvement and implementation process of an autonomous ESDP structure. The aim of these two chapters was to explain how the ESDP evolved outside of the NATO and why the EU accelerated its capability development process. And third chapter of this study focuses on Turkey’s role during the development process of ESDP. In order to explain Turkey’s role, the factors which make Turkey an important actor in European are assessed. Turkey’s exclusion from the European security system and its reactions to the ESDP are also covered within the study.
Keywords: Güvenlik_Avrupa Birliği; Türkiye_Avrupa Birliği